Navigating a path: multidisciplinary perspectives on transitions in sport coaching - Dieffenbach, K.; Blackett, A.; Rynne, S.; Chroni, S. (International Sport Coaching Journal, 2025)
This editorial for the Special Issue on Coaching Transitions in Sport highlights the importance of understanding the range of within-sport career transitions individuals experience while moving into and throughout their careers. Currently, the ways in which coaches adapt, evolve, and sustain their roles amid diverse and often complex career transitions have been largely unexamined. While other research has centered largely on topics such as coach effectiveness, stress, burnout, and well-being, this issue takes a multidisciplinary approach to broaden our understanding of coaching careers, focusing on transitions that occur over time and across contexts. Drawing on perspectives from psychology, sociology, pedagogy, and management, the manuscripts in this Special Issue provide much-needed insights into how coaching transitions are influenced by factors such as organizational support, interpersonal relationships, and cultural expectations. To grow this field of study, future research must examine diverse contexts beyond elite sport, incorporate experiences from marginalized groups, explore institutional and policy impacts, and consider the personal and systemic impacts of transitions. The cumulative impact of this Special Issue is intended to be the stimulation of a more comprehensive and supportive approach to coaching development, as well as continued interest in conducting research in this area.